Does Heterogeneous Strain Act as a Control on Seismic Anisotropy in Earth’s Lower Mantle? - Couper, Samantha; Speziale, Sergio; Marquardt, Hauke; Liermann, Hanns-Peter; Miyagi, Lowell (Frontiers in Earth Science, 2020)
Plastic deformation and texture development in minerals of the lower mantle can result in seismic anisotropy, and studying deformation of lower mantle materials is therefore important for interpreting lower mantle flow. Most previous deformation experiments documenting texture development at lower mantle pressures have been conducted on single-phase samples and/or at room temperature. However, real rocks deform at high temperature and are poly-phase and deformation is therefore likely different from that of a single phase. Here we report on high temperature diamond anvil cell deformation experiments on a multiphase assemblage of bridgmanite, ferropericlase, and ringwoodite compressed from ~28 to ~39 GPa and resistively heated at a constant temperature of 1000 K. We employ the elasto-viscoplastic self-consistent (EVPSC) method to model both texture and lattice strain of bridgmanite as a function of deformation mechanisms. Simulations indicate deformation of bridgmanite is accommodated by about half of slip activity on (100)[010] with the remainder split between (100)[001] and/or (100)<011>. Texture in bridgmanite is consistent with most seismic observations in the lowermost mantle. Although there is texture development in both bridgmanite and ringwoodite, ferropericlase does not develop coherent texture throughout the course of the experiment. Analysis of lattice strains suggests that the lack of coherent texture development in ferropericlase is due to heterogeneous plastic deformation resulting from microstructural interactions imposed by other phases. Variations in texturing of bridgmanite and ferropericlase could therefore cause laterally varying, complex anisotropy. Our models for binary mantle-like mixtures of bridgmanite and ferropericlase show that changes in strain and texture partitioning can explain the range of observed lower mantle anisotropies.